Causal effect of income on health: Investigating two closely related policy reforms in Austria - Mario Schnalzenberger (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2011)
I investigate the effect of income on mortality of the pensioners, comparing three subsequent policy periods in Austria. The pensioners who retired in the second period received 25% lower pension than those in the first period. This reduction in income was removed in the third policy period. These two reforms allow a causal identification of the effect of income on health. I estimate that lower pension did not change the mortality rate. The results are confirmed using both experiments and different methods of estimation. Furthermore, with regard to the expenditure on health services, I get that only prescribed drug consumption increased, with the remaining analyzed factors being unaffected.
Keywords: I12; J14; H55; 330; Income; Mortality; Health; Expenditure